Advances in Management Engineering - Hernández, Cesáreo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book deals with research in open challenges in Management Engineering in the 21st century, as well as selected opportunities and solutions to remedy them. Management Engineering is an emerging field that extends the analytical methods used in traditional Industrial Engineering and Industrial Organization to address the economic, behavioral and social dimensions of companies and their environments. Management Engineering extends its domain beyond the firm and the market to encompass the modeling and policy design of physical landscapes populated by social agents. The developments of the 21st century have made it necessary to adopt an integrative and global view of the different methodologies and tools that facilitate managers' decision-making processes, ranging from the strategic to the operational level. This book equips readers with precisely these urgently needed resources.
Part I: Management Engineering and Organizational Sciences -- Chapter 1. The Evolution and Classification of Management and Organizational Sciences. A Personal Interpretation -- Chapter 2. An Approach to the Industrial Organization Engineering Background in Spain -- Chapter 3. Sixty Years of Economics: Some Lessons for the Future -- Chapter 4. The New Industrial Organization -- Part II: The Governance System of the Firm -- Chapter 5. The Application of the Viable System Model to Enhance Organizational Resilience -- Chapter 6. Supply Chain Management: The Systemic Challenge -- Chapter 7. Project Management Methodologies in the Fourth Technological Revolution -- Chapter 8. Knowledge and Innovation in the New Industrial Organization -- Chapter 9. Institutional Endowment and Innovation Strategies -- Part III: Heuristics, Intelligent Systems and Agent Based Modelling -- Chapter 10. A Critical Sight to the NEH Heuristic -- Chapter 11. A Brief Introduction to the Use of Machine Learning Techniques in theAnalysis of Agent-Based Models -- Chapter 12. Emergence, Culture and Organizational Structure -- Chapter 13. A Study of the Innovative Applications of Intelligent Transport Systems Works to Logistics and Freight Transport: Public-Private Collaboration Projects -- Part IV: Innovative Teaching Activities in Management Engineering -- Chapter 14. Lean School: A Practical Space of Cooperative Learning from the Factory to the University -- Chapter 15. A Review of the Innovative Teaching Activities Carried Out by the School of Industrial Engineering of the University of Valladolid in the Field of Business Organization.
Keywords: Industrial engineering; Production engineering; Engineering design; Industrial organization; Production management; Industrial and Production Engineering; Engineering Design; Industrial Organization; Operations Management